Analysis of Istifham Sentences in QS. At-Tin Verse 8: A Study of Charles Sanders Peirce’s Semiotics - Ashri, Zainul (Universitas Ahmad Dahlan, 2023)
Istifham sentence is not always a question sentence that requires an answer. On the contrary, interogative sentence can function as a command sentence, news sentence and prohibition sentence. In balagah science, this kind of question sentence is classified as a majazi istifham sentence. It is a polemic in the academic world when balagah science cannot axplain the change of sentence function more clearly, only providing a theory when there are interogative sentence particles, such as the word “hamzah (اَ)” or “hal (هَلْ)” in verse. Therefore, this paper wants to explore in more detel the causes of the change of function of istifham setences using Peirce’s semiotic method. Where the concept of Peirce’s semiotics is a process of interpretation derived from the semiotic process of objects and representations which will produce interpretants. With the concept of Peirce’s semiotics, this paper focuses on exploring the interpretant of the istifham sentence in QS. At-Tin Verse 8. By using literature study and descriptive-analysis, the results of this research show that QS. At-Tin verse 8 as an example of an istifham sentence when studied with Peirce’s semiotic theory will find three interpretations. First, the istifham sentence in the verse is included in a potential question sentence that is still waiting for confirmation of the possibilities that exist. Second, the istifham sentence is included in the majazi istifham which gives the meaning of the statement and it’s factual nature, it’s factuality has been recognized in the science of balagah, and Third, as an affirmation that the fairest judge and justice is found from Allah Swt, where this is conventional which is found from the semiotic process of objects and representations of the previous verses.